Lentivirus-mediated RNA interference targeting HMGB1 modulates AQP1 to reduce pain induced by chronic compression of the dorsal root ganglia - Li, Jinlu; Yang, Kaihong; Yao, Fuchao; Wei, Hui (Frontiers in Pharmacology, 2024)
Backgrounds： Neuropathic pain (NP) is a kind of chronic pain that has attracted much attention in clinical practice, characterized by high morbidity, complex mechanisms, and difficulties in clinical treatment, with which the activation of High mobility group box 1（HMGB1） is closely related. The aim of this study was to investigate the effects of lentivirus-mediated RNA interference gene therapy targeting HMGB1 on neuropathic pain in rats with chronic dorsal root ganglion compression (CCD) and its specific mechanisms, so as to explore new pharmacological targets. Methods： Adult male Wistar rats were surgically subjected to chronic compression of the dorsal root ganglia (CCD). Behavioral tests were performed by calculating the paw withdrawal mechanical threshold (PWMT) and the thermal paw withdrawal latency (TPWL). Co-immunoprecipitation (CO-IP) was used to clarify protein interactions. Gene silencing was induced by injecting lentivirus expressing HMGB1 short hairpin RNA (shRNA) into rats. An LPS-inflammation-stimulated rat astrocyte model was established to validate the animal experiment results further. Western blot analysis and real-time quantitative PCR were used to detect pathway protein expression. Results： After first establishing the rat CCD model, both PWMT and PTWL were significantly reduced in rats, indicating that the model construction was successful. After lentiviral silencing of HMGB1 expression, NP was significantly alleviated in CCD rats. CO-IP experiments showed a link between HMGB1 and AQP1; After silencing HMGB1 expression, the expression of AQP1 was significantly reduced, and HMGB1 was able to modulate the effect of AQP1 on NP. Further use of an inhibitor of the HMGB1 receptor showed that after inhibition of RAGE, AQP1 was significantly reduced; HMGB1 may regulate AQP1 through its receptor RAGE to affect NP. Silencing of HMGB1 resulted in a significant decrease in NF-κB, and HMGB1 affects the inflammatory pathways it mediates. After silencing AQP1, NF-κB also decreased significantly, indicating that AQP1 is an upstream regulator of NF-κB. Conclusions： Lentivirus-mediated RNA interference (RNAi) silencing targeting HMGB1 may play a key role in the development of neuropathic pain in rats by regulating AQP1 expression via RAGE and ultimately activating NF-κB.